KEY PROBLEMS IN THE DEVELOPMENT OF TRANSPORT CORRIDORS IN CENTRAL ASIA AND WAYS TO SOLVE THEM - Азимов Хазрат (Journals Park Publishing, 2025)
The article is devoted to the analysis of the key problems of the development of international transport corridors in Central Asia and possible ways to solve them. Systemic obstacles, including high logistics costs, lack of direct access to seaports, inefficiency of customs administration and fragmentation of tariff policy, are considered. Special attention is paid to the prospects of digitalization of transport processes, the introduction of the "single window" system, the unification of tariffs and development of multimodal routes. The article examines the main transport corridors affecting the region, including the Trans-Caspian International Route, the North-South Corridor and the China-Kyrgyzstan-Uzbekistan Railway. It is concluded that comprehensive modernization of infrastructure, coordination of regional policy and integration into international logistics networks contribute to increasing the competitiveness of the Central Asian countries and strengthening their transit potential.
Keywords: Transport corridors, Central Asia, logistics, multimodal transportation, digitalization, customs procedures, tariff policy, Trans-Caspian route, North-South, China-Kyrgyzstan-Uzbekistan.